Graphene foam as a biocompatible scaffold for culturing human neurons. Issue 3 (7th March 2018) - D'Abaco, Giovanna M.; Mattei, Cristiana; Nasr, Babak; Hudson, Emma J.; Alshawaf, Abdullah J.; Chana, Gursharan; Everall, Ian P.; Nayagam, Bryony; Dottori, Mirella; Skafidas, Efstratios
Abstract : In this study, we explore the use of electrically active graphene foam as a scaffold for the culture of human-derived neurons. Human embryonic stem cell (hESC)-derived cortical neurons fated as either glutamatergic or GABAergic neuronal phenotypes were cultured on graphene foam. We show that graphene foam is biocompatible for the culture of human neurons, capable of supporting cell viability and differentiation of hESC-derived cortical neurons. Based on the findings, we propose that graphene foam represents a suitable scaffold for engineering neuronal tissue and warrants further investigation as a model for understanding neuronal maturation, function and circuit formation.